Low tube voltage prospectively ECG-triggered coronary CT angiography: A systematic review of image quality and radiation dose - Tan, S.; Yeong, C.; Raja Aman, R.; Ng, K.; Abdul Aziz, Y.; Chee, K.; Sun, Zhonghua (British Institute of Radiology, 2018)
OBJECTIVE: This study aimed (1) to perform a systematic review on scanning parameters and contrast medium (CM) reduction methods used in prospectively ECG-triggered low tube voltage coronary CT angiography (CCTA), (2) to compare the achievable dose reduction and image quality, and (3) to propose appropriate scanning techniques and CM administration methods. METHODS: A systematic search were performed in PubMed, the Cochrane library, CINAHL, Web of Science, ScienceDirect and Scopus, where 20 studies were selected for analysis of scanning parameters and CM reduction methods. RESULTS: The mean effective dose (HE) ranged from 0.31 to 2.75 mSv at 80 kVp, 0.69 to 6.29 mSv at 100 kVp, and 1.53 to 10.7 mSv at 120 kVp. Radiation dose reductions of 38 to 83 % at 80 kVp and 3 to 80 % at 100 kVp could be achieved with preserved image quality. Similar vessel contrast enhancement to 120 kVp could be obtained by applying iodine delivery rate (IDR) of 1.35 to 1.45 gs-1 with total iodine dose (TID) of between 10.9 and 16.2 g at 80 kVp, and IDR of 1.08 to 1.70 gs-1 with TID of between 18.9 and 20.9 g at 100 kVp. CONCLUSION: This systematic review found that radiation doses could be reduced between 38 to 83 % at 80 kVp, and 3 to 80 % at 100 kVp without compromising the image quality. Advances in knowledge: The suggested appropriate scanning parameters and CM reduction methods can be used to help users in achieving diagnostic image quality with reduced radiation dose.